Advances in diffuse malignant peritoneal mesothelioma - Tristan D. Yan; Raffit Hassan; Laura Welch; Paul H. Sugarbaker (Frontiers Media S.A., 2011)
Malignant mesothelioma is a highly aggressive neoplasm. The incidence of malignant mesothelioma is increasing worldwide. Diffuse malignant peritoneal mesothelioma (DMPM) represents one-fourth of all mesotheliomas. Association of asbestos exposure with DMPM has been observed, especially in males. A great majority of patients present with abdominal pain and distension, caused by accumulation of tumors and ascitic fluid. In the past, DMPM was considered a pre-terminal condition; therefore attracted little attention. Patients invariably died from their disease within a year. Recently, several prospective trials have demonstrated median survival of 40 to 90 months and 5-year survival of 30% to 60% after the combined treatment using cytoreductive surgery and perioperative intraperitoneal chemotherapy. This improvement in survival has prompted new searches into the medical science related to DMPM, a disease previously ignored as uninteresting. This review article focuses on the key advances in the epidemiology, diagnosis, staging, treatments and prognosis of DMPM that have occurred in the past decade.